(untitled) (Eurasian Scientific Herald, 2022)
Nowadays, a lot of attention is paid to teaching children foreign languages. Particular emphasis is placed on English, German, Spanish and French, which have become the world’s languages. This article focuses on cultivating tolerance in foreign language learning and illustrating their models.